A NEW APPROACH TO PEDAGOGICAL CONTROL OF THE PROFESSIONAL ACTIVITY OF A TEACHER OF TECHNOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The methods of studying, analysis and pedagogical control of the professional activity of a teacher of technology are considered.